Gastrointestinal stromal tumors (GISTs) at uncommon locations: A large population based analysis. Issue 6 (5th January 2015) - Kukar, Moshim; Kapil, Aditi; Papenfuss, Wesley; Groman, Adrienne; Grobmyer, Stephen R.; Hochwald, Steven N.
Abstract : Introduction: Sparse information is available about GISTs in uncommon locations. Our large database analysis aims to determine the characteristics of GISTs in the esophagus, colon and rectum and compare to gastric GISTs. Methods: The Surveillance Epidemiology and End Results (SEER) database was queried from 1990 to 2009 using CS SCHEMA v0203. Characteristics of each location were compared to gastric GISTs. Results: 4411 GIST (29 esophageal, 2658 stomach, 1463 small intestine, 126 colonic, and 135 rectal) from 1990 to 2009 were identified. Univariate and multivariate predictors of worse disease specific survival in both the entire cohort and surgical resection group include older age, male gender, tumor size > 5cm, no surgical intervention and anatomical location. Although less likely to undergo surgical resection, esophageal GIST (all patients and resected) had a comparable survival to gastric GIST. A higher proportion of colonic GISTs presented with distant disease and had a worse disease specific survival when compared to rectal GISTs. Conclusion: Our results show a rising incidence in GISTs and highlight the characteristics of GISTs based on anatomical location. In addition, this is the first study to demonstrate that colonic GISTs behave differently when compared to rectal GISTs and warrants further prospective evaluation. J. Surg. Oncol. 2015 111:696–701 . © 2015 Wiley Periodicals, Inc.